Underwater adhesive, preparation method thereof and underwater equipment

Through a new underwater adhesive preparation method, cross-linking and polymerization is used for raw materials such as polymer monomers, ionic liquid monomers and cationic polymers, the problems of debonding and attenuation of the existing underwater adhesives when used in water are solved, and efficient and long-term underwater adhesives are achieved.

CN119592266APending Publication Date: 2025-03-11SHENZHEN ADVANCED POLYMER MATERIALS RES INST
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411933376.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

When used in water, existing underwater adhesives have problems such as debonding, attenuation of adhesive properties, short operating intervals, and the need for additional curing conditions and long curing and setting time.

Method used

By using a preparation method of an underwater adhesive, a raw material including a first polymer monomer, a first ionic liquid monomer and/or a first cationic polymer, a first crosslinking agent, a first initiator, and an organic solvent is mixed, and a low molecular weight polymer is reacted under a protective atmosphere, and then a second reaction is mixed with a second polymer monomer, a second ionic liquid monomer and/or a second cationic polymer, a second crosslinking agent and a second initiator to obtain an underwater adhesive having excellent adhesive properties and water resistance.

Benefits of technology

The underwater adhesive has strong instantaneous surface wetting ability and high colloidal cohesion, exhibits excellent adhesive properties and has long-term water resistance. It is suitable for permanent bonding, sealing and repairing in water and building permanent waterproof and moisture-proof sealing structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119592266A_ABST
    Figure CN119592266A_ABST
Patent Text Reader

Abstract

The invention provides an underwater adhesive, a preparation method thereof and underwater equipment, and relates to the field of materials. The preparation method comprises the following steps: mixing a first polymer monomer, a first ionic liquid monomer and / or a first cationic polymer, a cross-linking agent, an initiator and an organic solvent, and reacting to obtain a low-molecular-weight polymer; and mixing the low-molecular-weight polymer, a second polymer monomer, a second ionic liquid monomer and / or a second cationic polymer, a cross-linking agent and an initiator to obtain a precursor solution, and reacting to obtain the underwater adhesive. The underwater adhesive provided by the invention belongs to a binary supramolecular adhesive capable of being used for underwater adhesion, the adhesive is formed by cross-linking polymerization of a low-molecular-weight straight chain and various monomers, a colloid not only keeps high fluidity of the straight chain, but also has strong cohesive force due to interaction generated in a cross-linked network, and the adhesive can be used for underwater adhesion. The two components are combined, so that the adhesive has strong instantaneous surface infiltration capacity and high colloid cohesion, and shows excellent adhesive performance on various surfaces.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of materials, and in particular to an underwater adhesive and a preparation method thereof and underwater equipment. Background Art

[0002] Underwater adhesives are widely used in daily life, construction projects and emergency rescue, including civil air defense projects, underground buildings and tunnels, underwater repair, salvage and rescue, ocean engineering, marine industry, etc. Conventional adhesives cannot be used directly in an underwater environment because a water film layer will form on the surface during underwater bonding, which cannot form a high-strength effect with the interface, and there are problems such as debonding and severe attenuation of bonding performance. Secondly, conventional adhesives are easy to swell in water and are not water-resistant, and cannot maintain high-strength bonding performance for a long time in a humid or underwater environment. To solve the above problems, a common idea is to introduce hydrophobic groups into the molecular chain to improve water resistance. However, too many hydrophobic groups will cause the adhesive to have poor bonding performance on substrates such as glass and metal. At present, the mainstream underwater adhesives are moisture-cured polyurethane or two-component epoxy resin sealants, which are known for their excellent strength, hardness and impact resistance, but have the disadvantages of short operating range during underwater operations, requiring additional curing conditions and long curing time, which are extremely inconvenient to use.

[0003] In recent years, a series of adhesives based on pressure-sensitive adhesives have been developed, which show excellent bonding properties through non-covalent interactions such as hydrogen bonding, cation-π, π-π and other synergistic effects. However, these adhesives either require solvent dispersion to fit the bonding surface due to the introduction of high Tg monomers; or are prone to plasticization or swelling due to the high proportion of hydrophilic groups; and the surface wetting ability and colloid cohesive strength cannot be balanced, both of which limit the application of such adhesives in underwater applications. Summary of the invention

[0004] The purpose of this application is to provide an underwater adhesive and a preparation method thereof and underwater equipment to solve the above problems.

[0005] To achieve the above objectives, this application adopts the following technical solutions:

[0006] A method for preparing an underwater adhesive, comprising:

[0007] Mixing raw materials including a first polymer monomer, a first ionic liquid monomer and / or a first cationic polymer, a first crosslinking agent, a first initiator, and an organic solvent, and performing a first reaction under a protective atmosphere to obtain a low molecular weight polymer;

[0008] The low molecular weight polymer, the second polymer monomer, the second ionic liquid monomer and / or the second cationic polymer, the second crosslinking agent and the second initiator are mixed to obtain a precursor solution, and then a second reaction is performed to obtain the underwater adhesive;

[0009] The first polymer monomer and the second polymer monomer each independently include one or more hydrophobic acrylic compounds; the first ionic liquid monomer and the second ionic liquid monomer each independently include one or more imide salts containing a double bond structure; the first cationic polymer and the second cationic polymer each independently include one or more polyquaternary ammonium salts containing a double bond structure; the weight average molecular weight of the low molecular weight polymer is 1-50kDa.

[0010] Preferably, the method for preparing the underwater adhesive satisfies one or more of the following conditions:

[0011] (1) the first polymer monomer and the second polymer monomer each independently include one or more of benzyl acrylate, butyl acrylate, methyl acrylate, ethyl acrylate, cyclohexyl acrylate, ethyl methacrylate, butyl methacrylate, isopropyl methacrylate, isobornyl methacrylate, glycidyl methacrylate, methyl methacrylate, and benzyl methacrylate;

[0012] (2) the first ionic liquid monomer and the second ionic liquid monomer each independently include one or more of acryloylalkyl trimethyl ammonium bis (trifluoromethanesulfonyl) imide salt, acryloyloxyethyl trimethyl ammonium bis (trifluoromethanesulfonyl) imide salt, methacryloyloxyethyl trimethyl ammonium bis (trifluoromethanesulfonyl) imide salt, and methacrylamide propyl ammonium bis (trifluoromethanesulfonyl) imide salt;

[0013] (3) the first cationic polymer and the second cationic polymer each independently include one or more of polyquaternium-32, polyquaternium-28, and polyquaternium-51;

[0014] (4) the first cross-linking agent and the second cross-linking agent each independently include one or more of an acrylate cross-linking agent and an acrylamide cross-linking agent;

[0015] (5) the first initiator and the second initiator independently include one or more of a thermal initiator and a photoinitiator;

[0016] (6) The organic solvent includes one or more of toluene, heptane, ethyl acetate, tetrahydrofuran, a heptane to toluene solution in a mass ratio of 1:(1-4), an ethyl acetate to toluene solution in a mass ratio of 1:(1-2), ethanol, dichloromethane, and chloroform.

[0017] Preferably, the method for preparing the underwater adhesive satisfies one or more of the following conditions:

[0018] (1) The acrylate crosslinking agent includes one or more of 1,3-propylene glycol diacrylate, 1,4-butanediol diacrylate, 1,6-hexanediol diacrylate, ethylene glycol dimethacrylate, and ethylene glycol diacrylate;

[0019] (2) The acrylamide cross-linking agent includes methylene bisacrylamide;

[0020] (3) The first initiator is a thermal initiator, and the second initiator is a photoinitiator;

[0021] (4) The thermal initiator includes one or more of azobisisobutyronitrile, azobisisovaleronitrile, azobisisoheptylnitrile, dimethyl azobisisobutyrate, 1-(cyano-1-methylethylazo)formamide, 1,1'-azo(cyanocyclohexane), dibenzoyl peroxide, diisopropylbenzene peroxide, and methyl ethyl ketone peroxide;

[0022] (5) The photoinitiator includes one or more of 1-hydroxy-cyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, 2,4,6-trimethylbenzoyl diphenyl phosphine oxide, 2,4,6-trimethylbenzoyl phosphonic acid ethyl ester, 2-methyl-1-[4-methylthiophenyl]-2-morpholinyl-1-propanone, 2-isopropylthioxanthone, 4-dimethylamino-benzoic acid ethyl ester, benzoin dimethyl ether, methyl o-benzoylbenzoate, 4-chlorobenzophenone, 4-phenylbenzophenone, and 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone.

[0023] Preferably, the method for preparing the underwater adhesive satisfies one or more of the following conditions:

[0024] (1) the molar ratio of the first polymer monomer to the first ionic liquid monomer and / or the first cationic polymer, and the molar ratio of the second polymer monomer to the second ionic liquid monomer and / or the second cationic polymer are each independently (3-9): 1;

[0025] (2) the amount of the first crosslinking agent is no more than 1% of the total molar amount of the first polymer monomer, the first ionic liquid monomer and / or the first cationic polymer;

[0026] (3) the amount of the second crosslinking agent is no more than 1% of the total molar amount of the second polymer monomer, the second ionic liquid monomer and / or the second cationic polymer;

[0027] (4) the amount of the first initiator is 0.01% to 10% of the total molar amount of the first polymer monomer, the first ionic liquid monomer and / or the first cationic polymer;

[0028] (5) the amount of the second initiator is 0.01% to 10% of the total molar amount of the second polymer monomer, the second ionic liquid monomer and / or the second cationic polymer;

[0029] (6) The molar ratio of the low molecular weight polymer to the second polymer monomer is 1:(0.1-4).

[0030] Preferably, the method for preparing the underwater adhesive satisfies one or more of the following conditions:

[0031] (1) the molar ratio of the first polymer monomer to the first ionic liquid monomer and / or the first cationic polymer, and the molar ratio of the second polymer monomer to the second ionic liquid monomer and / or the second cationic polymer are each independently (5-7): 1;

[0032] (2) the amount of the first crosslinking agent is no more than 0.5% of the total molar amount of the first polymer monomer, the first ionic liquid monomer and / or the first cationic polymer;

[0033] (3) the amount of the second crosslinking agent is no more than 0.5% of the total molar amount of the second polymer monomer, the second ionic liquid monomer and / or the second cationic polymer;

[0034] (4) the amount of the first initiator is 1% of the total molar amount of the first polymer monomer, the first ionic liquid monomer and / or the first cationic polymer;

[0035] (5) the amount of the second initiator is 1% of the total molar amount of the second polymer monomer, the second ionic liquid monomer and / or the second cationic polymer;

[0036] (6) The molar ratio of the low molecular weight polymer to the second polymer monomer is 1:(0.5-1.5).

[0037] Preferably, the method for preparing the underwater adhesive satisfies one or more of the following conditions:

[0038] (1) The first reaction is thermally initiated, with a reaction temperature of 40-110° C. and a reaction time of 1-24 h;

[0039] (2) The second reaction is photoinduced with a power density of 1-1000 mW / cm 2 , wavelength 200-450nm, time 0.001-6h;

[0040] (3) The weight average molecular weight of the low molecular weight polymer is 5-20 kDa;

[0041] (4) During the first reaction, the total solid content is 15%-45%, preferably 20%-30%;

[0042] (5) Before carrying out the first reaction, the system is deoxygenated.

[0043] Preferably, after the first reaction is completed, the step further includes: transferring the reaction product into a detergent for precipitation and vacuum drying;

[0044] and / or,

[0045] The precursor solution is coated on the base film to obtain a wet film, and then the second reaction is carried out, and constant temperature vacuum drying is performed to obtain the adhesive.

[0046] Preferably, the method for preparing the underwater adhesive satisfies one or more of the following conditions:

[0047] (1) The detergent comprises a mixture of a polar solvent and a non-polar solvent in a mass ratio of 1:(5-10); the polar solvent comprises methanol and / or ethanol, and the non-polar solvent comprises one or more of cyclohexane, n-hexane, and petroleum ether;

[0048] (2) The vacuum degree of the vacuum drying is 0.1-1000 Pa, the temperature is 40-80° C., and the time is 6-24 h;

[0049] (3) The thickness of the wet film is 1-1000 μm, preferably 25-250 μm;

[0050] (4) The base film comprises one or more of PP, PC, PVC, PET, and metal foil, and has a thickness of 25-250 μm;

[0051] (5) The temperature of the constant temperature vacuum drying is 30-80°C and the time is 0.5-30min.

[0052] The present application also provides an underwater adhesive, which is prepared using the underwater adhesive preparation method.

[0053] The present application also provides an underwater device, comprising the underwater adhesive.

[0054] Compared with the prior art, the beneficial effects of this application include:

[0055] The underwater adhesive provided by the present application is a binary supramolecular adhesive that can be used for underwater bonding. The adhesive is formed by cross-linking and polymerization of low molecular weight straight chains and various monomers. The colloid not only retains the high fluidity of the straight chain, but also ensures that the colloid has strong cohesion due to the interaction generated in the cross-linked network. The combination of the two makes the adhesive have strong instantaneous surface wetting ability and high colloid cohesion, and exhibits excellent bonding performance on various surfaces; secondly, the fully hydrophobic structure makes the adhesive excellent in initial adhesion and drainage and long-term water resistance, and has the potential for long-term underwater service. The polymerization and coating process of the adhesive is simple and mature, and can be quickly industrialized and mass-produced; the adhesive can replace mechanical fasteners or liquid glues, and is suitable for permanent bonding, plugging and repair in water, or for building permanent waterproof and moisture-proof sealing structures. BRIEF DESCRIPTION OF THE DRAWINGS

[0056] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.

[0057] Figure 1 A schematic diagram of a method for preparing an underwater adhesive provided in an embodiment of the present application;

[0058] Figure 2 This is a comparison chart of the bonding performance of the samples in Example 1 on the surfaces of common materials;

[0059] Figure 3 It is a comparison chart of the bonding performance of each embodiment and comparative example 1 and comparative example 4;

[0060] Figure 4 This is the performance attenuation test chart of dry bonding after being immersed in tap water for 4 weeks;

[0061] Figure 5 This is a performance attenuation test chart after immersion in tap water for 4 weeks;

[0062] Figure 6 This is a test chart showing the effect of the ratio of low molecular weight polymer to cross-linking monomer on the bonding performance of materials;

[0063] Figure 7 This is a test chart of the effect of UV curing machine power on material bonding performance;

[0064] Figure 8 This is a performance comparison chart of this material and other commercially available products with excellent performance. DETAILED DESCRIPTION

[0065] In order to better explain the technical solution provided by this application, before the embodiments, the technical solution is first described as a whole, as follows:

[0066] A method for preparing an underwater adhesive, comprising:

[0067] Mixing raw materials including a first polymer monomer, a first ionic liquid monomer and / or a first cationic polymer (it should be noted that the first ionic liquid monomer and the first cationic polymer are regarded as a whole, that is, the first ionic liquid monomer and the first cationic polymer can exist simultaneously or separately, and together with the first polymer monomer, the first cross-linking agent, the first initiator and the organic solvent, serve as system raw materials for the first reaction), the first cross-linking agent, the first initiator and the organic solvent, and performing a first reaction under a protective atmosphere to obtain a low molecular weight polymer;

[0068] The low molecular weight polymer, the second polymer monomer, the second ionic liquid monomer and / or the second cationic polymer (it should be noted that the second ionic liquid monomer and the second cationic polymer are regarded as a whole, that is, the second ionic liquid monomer and the second cationic polymer can exist simultaneously or separately, and together with the second polymer monomer, the second crosslinking agent and the second initiator, serve as the raw materials of the second reaction system), the second crosslinking agent and the second initiator are mixed to obtain a precursor solution, and then a second reaction is carried out to obtain the underwater adhesive;

[0069] The first polymer monomer and the second polymer monomer each independently include one or more hydrophobic acrylic compounds; the first ionic liquid monomer and the second ionic liquid monomer each independently include one or more imide salts containing a double bond structure; the first cationic polymer and the second cationic polymer each independently include one or more polyquaternary ammonium salts containing a double bond structure; the weight average molecular weight of the low molecular weight polymer is 1-50kDa.

[0070] Optionally, the weight average molecular weight of the low molecular weight polymer may be 1 kDa, 5 kDa, 10 kDa, 20 kDa, 30 kDa, 40 kDa, 50 kDa or any value between 0.1-50 kDa.

[0071] In an optional embodiment, the first polymer monomer and the second polymer monomer each independently include one or more of benzyl acrylate, butyl acrylate, methyl acrylate, ethyl acrylate, cyclohexyl acrylate, ethyl methacrylate, butyl methacrylate, isopropyl methacrylate, isobornyl methacrylate, glycidyl methacrylate, methyl methacrylate, and benzyl methacrylate;

[0072] In an optional embodiment, the first ionic liquid monomer and the second ionic liquid monomer each independently include one or more of acryloylalkyl trimethyl ammonium bis (trifluoromethanesulfonyl) imide salt, acryloyloxyethyl trimethyl ammonium bis (trifluoromethanesulfonyl) imide salt, methacryloyloxyethyl trimethyl ammonium bis (trifluoromethanesulfonyl) imide salt, and methacrylamide propyl ammonium bis (trifluoromethanesulfonyl) imide salt;

[0073] In an optional embodiment, the first cationic polymer and the second cationic polymer each independently include one or more of polyquaternium-32, polyquaternium-28, and polyquaternium-51;

[0074] In an optional embodiment, the first cross-linking agent and the second cross-linking agent each independently include one or more of an acrylate cross-linking agent and an acrylamide cross-linking agent;

[0075] In an optional embodiment, the first initiator and the second initiator each independently include one or more of a thermal initiator and a photoinitiator;

[0076] In an optional embodiment, the organic solvent includes one or more of toluene, heptane, ethyl acetate, tetrahydrofuran, a heptane and toluene solution in a mass ratio of 1:(1-4), an ethyl acetate and toluene solution in a mass ratio of 1:(1-2), ethanol, dichloromethane, and chloroform.

[0077] Optionally, the mass ratio of heptane to toluene may be 1:1, 1:2, 1:3, 1:4 or any value between 1:(1-4), and the mass ratio of ethyl acetate to toluene may be 1:1, 1:1.5, 1:2 or any value between 1:(1-2);

[0078] In an optional embodiment, the acrylate crosslinking agent includes one or more of 1,3-propylene glycol diacrylate, 1,4-butanediol diacrylate, 1,6-hexanediol diacrylate, ethylene glycol dimethacrylate, and ethylene glycol diacrylate;

[0079] In an optional embodiment, the acrylamide cross-linking agent includes methylene bisacrylamide;

[0080] In an optional embodiment, the first initiator is a thermal initiator, and the second initiator is a photoinitiator;

[0081] In an optional embodiment, the thermal initiator includes one or more of azobisisobutyronitrile, azobisisovaleronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, 1-(cyano-1-methylethylazo)formamide, 1,1'-azo(cyanocyclohexane), dibenzoyl peroxide, diisopropylbenzene peroxide, and methyl ethyl ketone peroxide;

[0082] In an optional embodiment, the photoinitiator includes 1-hydroxy-cyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, 2,4,6 (trimethylbenzoyl) diphenyl phosphine oxide, 2,4,6-trimethylbenzoyl phosphonic acid ethyl ester, 2-methyl-1-[4-methylthiophenyl]-2-morpholinyl-1-propanone, 2-isopropylthioxanthone, 4-dimethylamino-benzoic acid ethyl ester, benzoin dimethyl ether, methyl o-benzoylbenzoate, 4-chlorobenzophenone, 4-phenylbenzophenone, 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone One or more.

[0083] In an optional embodiment, the molar ratio of the first polymer monomer to the first ionic liquid monomer and / or the first cationic polymer, and the molar ratio of the second polymer monomer to the second ionic liquid monomer and / or the second cationic polymer are each independently (3-9): 1;

[0084] Optionally, the molar ratio of the first polymer monomer to the first ionic liquid monomer and / or the first cationic polymer, and the molar ratio of the second polymer monomer to the second ionic liquid monomer and / or the second cationic polymer can be independently 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1 or any value between (3-9):1;

[0085] In an optional embodiment, the amount of the first crosslinking agent is no more than 1% of the total molar amount of the first polymer monomer, the first ionic liquid monomer and / or the first cationic polymer;

[0086] Optionally, the amount of the first cross-linking agent may be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1% or any value not greater than 1% of the total molar amount of the first polymer monomer, the first ionic liquid monomer and / or the first cationic polymer;

[0087] In an optional embodiment, the amount of the second crosslinking agent is no more than 1% of the total molar amount of the second polymer monomer, the second ionic liquid monomer and / or the second cationic polymer;

[0088] Optionally, the amount of the second cross-linking agent can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1% or any value not greater than 1% of the total molar amount of the second polymer monomer, the second ionic liquid monomer and / or the second cationic polymer;

[0089] In an optional embodiment, the amount of the first initiator is 0.01%-10% of the total molar amount of the first polymer monomer, the first ionic liquid monomer and / or the first cationic polymer;

[0090] Optionally, the amount of the first initiator can be 0.01%, 0.05%, 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or any value between 0.01% and 10% of the total molar amount of the first polymer monomer, the first ionic liquid monomer and / or the first cationic polymer;

[0091] In an optional embodiment, the amount of the second initiator is 0.01%-10% of the total molar amount of the second polymer monomer, the second ionic liquid monomer and / or the second cationic polymer;

[0092] Optionally, the amount of the second initiator can be 0.01%, 0.05%, 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or any value between 0.01% and 10% of the total molar amount of the second polymer monomer, the second ionic liquid monomer and / or the second cationic polymer;

[0093] In an optional embodiment, the molar ratio of the low molecular weight polymer to the second polymer monomer is 1:(0.1-4).

[0094] Optionally, the molar ratio of the low molecular weight polymer to the second polymer monomer may be 1:0.1, 1:0.5, 1:1, 1:2, 1:3, 1:4 or any value between 1:(0.1-4).

[0095] In an optional embodiment, the molar ratio of the first polymer monomer to the first ionic liquid monomer and / or the first cationic polymer, and the molar ratio of the second polymer monomer to the second ionic liquid monomer and / or the second cationic polymer are each independently (5-7): 1;

[0096] In an optional embodiment, the amount of the first crosslinking agent is no more than 0.5% of the total molar amount of the first polymer monomer, the first ionic liquid monomer and / or the first cationic polymer;

[0097] In an optional embodiment, the amount of the second crosslinking agent is no more than 0.5% of the total molar amount of the second polymer monomer, the second ionic liquid monomer and / or the second cationic polymer;

[0098] In an optional embodiment, the amount of the first initiator is 1% of the total molar amount of the first polymer monomer, the first ionic liquid monomer and / or the first cationic polymer;

[0099] In an optional embodiment, the amount of the second initiator is 1% of the total molar amount of the second polymer monomer, the second ionic liquid monomer and / or the second cationic polymer;

[0100] In an optional embodiment, the molar ratio of the low molecular weight polymer to the second polymer monomer is 1:(0.5-1.5).

[0101] In an optional embodiment, the first reaction is thermally initiated, the reaction temperature is 40-110° C., and the time is 1-24 h;

[0102] Optionally, the first reaction is thermally initiated, the reaction temperature may be 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C or any value between 40-110°C, and the time may be 1h, 2h, 4h, 6h, 8h, 10h, 12h, 14h, 16h, 18h, 20h, 22h, 24h or any value between 1-24h;

[0103] In an optional embodiment, the second reaction is photoinduced with a power density of 1-1000 mW / cm 2 , wavelength 200-450nm, time 0.001-6h;

[0104] Optionally, the second reaction is photoinduced, and the power density can be 1 mW / cm 2 、10mW / cm 2 , 100mW / cm 2 , 500mW / cm 2 , 1000mW / cm 2 Or 1-1000mW / cm 2the wavelength may be 200nm, 250nm, 300nm, 350nm, 400nm, 450nm or any value between 200-450nm, and the time may be 0.001h, 0.005h, 0.01h, 0.05h, 0.1h, 0.5h, 1h, 2h, 3h, 4h, 5h, 6h or any value between 0.001-6h;

[0105] In an optional embodiment, the weight average molecular weight of the low molecular weight polymer is 5-20 kDa;

[0106] In an optional embodiment, during the first reaction, the total solid content is 15%-45%, preferably 20%-30%;

[0107] Optionally, during the first reaction, the total solid content may be 15%, 20%, 25%, 30%, 35%, 40%, 45% or any value between 15% and 45%;

[0108] In an optional embodiment, before carrying out the first reaction, the system is deoxygenated.

[0109] In an optional embodiment, after the first reaction is completed, the step further includes: transferring the reaction product into a detergent for precipitation and vacuum drying;

[0110] and / or,

[0111] The precursor solution is coated on the base film to obtain a wet film, and then the second reaction is carried out, and constant temperature vacuum drying is performed to obtain the adhesive.

[0112] In an optional embodiment, the detergent comprises a mixture of a polar solvent and a non-polar solvent in a mass ratio of 1:(5-10); the polar solvent comprises methanol and / or ethanol, and the non-polar solvent comprises one or more of cyclohexane, n-hexane, and petroleum ether;

[0113] Optionally, the mass ratio of the polar solvent to the non-polar solvent may be 1:5, 1:6, 1:7, 1:8, 1:9, 1:10 or any value between 1:(5-10);

[0114] In an optional embodiment, the vacuum degree of the vacuum drying is 0.1-1000 Pa, the temperature is 40-80° C., and the time is 6-24 h;

[0115] Optionally, the vacuum degree of the vacuum drying can be 0.1Pa, 1Pa, 10Pa, 100Pa, 500Pa, 1000Pa or any value between 0.1-1000Pa, the temperature can be 40°C, 50°C, 60°C, 70°C, 80°C or any value between 40-80°C, and the time can be 6h, 12h, 18h, 24h or any value between 6-24h;

[0116] In an optional embodiment, the thickness of the wet film is 1-1000 μm, preferably 25-250 μm;

[0117] Optionally, the thickness of the wet film may be 1 μm, 10 μm, 100 μm, 200 μm, 300 μm, 400 μm, 500 μm, 600 μm, 700 μm, 800 μm, 900 μm, 1000 μm or any value between 1 and 1000 μm;

[0118] In an optional embodiment, the base film includes one or more of PP, PC, PVC, PET, and metal foil, and has a thickness of 25-250 μm;

[0119] Optionally, the thickness of the base film may be 25 μm, 50 μm, 100 μm, 150 μm, 200 μm, 250 μm or any value between 25 and 250 μm;

[0120] In an optional embodiment, the constant temperature vacuum drying is performed at a temperature of 30-80° C. and a time of 0.5-30 min.

[0121] Optionally, the temperature of the constant temperature vacuum drying can be 30°C, 40°C, 50°C, 60°C, 70°C, 80°C or any value between 30-80°C, and the time can be 0.5min, 1min, 5min, 10min, 20min, 30min or any value between 0.5-30min.

[0122] The present application also provides an underwater adhesive, which is prepared using the underwater adhesive preparation method.

[0123] The present application also provides an underwater device, comprising the underwater adhesive.

[0124] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0125] Example 1

[0126] like Figure 1 As shown, this embodiment provides an underwater adhesive, and the preparation method is as follows:

[0127] 80 parts of butyl acrylate, 10 parts of benzyl acrylate, 10 parts of acryloyloxyethyl trimethyl ammonium bis (trifluoromethanesulfonyl) imide salt monomer and 1 part of azobisisobutyronitrile were dissolved in tetrahydrofuran, the solid content was controlled to be 25%, nitrogen was bubbled for deoxygenation for 1 hour, and then heated to 70°C for reaction for 12 hours under nitrogen environment. After the reaction was completed and cooled to room temperature, the product was transferred to a detergent (n-hexane: methanol = 8:2) for precipitation, and the precipitate was placed in a vacuum box and vacuum degassed and dried at 60°C for 12 hours to remove the solvent and volatile monomers to obtain a low molecular weight linear polymer. Every 80 parts of low molecular weight linear polymer is dissolved in 100 parts of monomer mixture (80 parts of butyl acrylate, 10 parts of benzyl acrylate, 10 parts of acryloyloxyethyl trimethyl ammonium bis (trifluoromethanesulfonyl) imide salt monomer), 1 part of 2,2-diethoxyacetophenone and 0.1 part of ethylene glycol diacrylate are added, and the mixture is fully stirred and evenly mixed, and nitrogen is bubbled to deoxidize for 1 hour to obtain a cross-linked network precursor solution. The precursor solution is coated on a single-sided release silicon-free PET by a coating machine with a wet film thickness of 150μm, and the step speed is controlled to 5m / min and transferred to a UV curing machine (main peak 365nm), and the lamp power is adjusted to 1kW, and then transferred to a 40°C vacuum constant temperature oven for drying and rolling to obtain the product.

[0128] Example 2

[0129] This embodiment provides an underwater adhesive, and the preparation method is as follows:

[0130] 80 parts of butyl acrylate, 10 parts of glycidyl methacrylate, 10 parts of acryloyloxyethyl trimethyl ammonium bis (trifluoromethanesulfonyl) imide salt monomer and 1 part of azobisisobutyronitrile were dissolved in tetrahydrofuran, the solid content was controlled to be 25%, nitrogen was bubbled for deoxygenation for 1 hour, and then heated to 70°C for reaction for 12 hours under nitrogen environment. After the reaction was completed and cooled to room temperature, the product was transferred to a detergent (n-hexane: methanol = 8:2) for precipitation, and the precipitate was placed in a vacuum box and vacuum degassed and dried at 60°C for 12 hours to remove the solvent and volatile monomers to obtain a low molecular weight linear polymer. Every 80 parts of low molecular weight linear polymer are dissolved in 100 parts of monomer mixture (80 parts of butyl acrylate, 10 parts of glycidyl methacrylate, 10 parts of acryloyloxyethyl trimethyl ammonium bis (trifluoromethanesulfonyl) imide salt monomer), 1 part of 2,2-diethoxyacetophenone and 0.1 part of ethylene glycol diacrylate are added, and the mixture is fully stirred and evenly mixed, and nitrogen is bubbled to deoxygenate for 1 hour to obtain a cross-linked network precursor solution. The precursor solution is coated on a single-sided release silicon-free PET by a coating machine with a wet film thickness of 150μm, and the step speed is controlled to 5m / min and transferred to a UV curing machine (main peak 365nm), and the lamp power is adjusted to 1kW, and then transferred to a 40°C vacuum constant temperature oven for drying and rolling to obtain the product.

[0131] Example 3

[0132] This embodiment provides an underwater adhesive, and the preparation method is as follows:

[0133] 80 parts of ethyl methacrylate, 10 parts of benzyl acrylate, 10 parts of acryloyloxyethyl trimethyl ammonium bis (trifluoromethanesulfonyl) imide salt monomer and 1 part of azobisisobutyronitrile were dissolved in tetrahydrofuran, the solid content was controlled to be 25%, nitrogen was bubbled for deoxygenation for 1 hour, and then heated to 70°C for reaction for 12 hours under nitrogen environment. After the reaction was completed and cooled to room temperature, the product was transferred to a detergent (n-hexane: methanol = 8:2) for precipitation, and the precipitate was placed in a vacuum box and vacuum degassed and dried at 60°C for 12 hours to remove the solvent and volatile monomers to obtain a low molecular weight linear polymer. Every 80 parts of low molecular weight linear polymer are dissolved in 100 parts of monomer mixture (80 parts of ethyl methacrylate, 10 parts of benzyl acrylate, 10 parts of acryloyloxyethyl trimethyl ammonium bis (trifluoromethanesulfonyl) imide salt monomer), 1 part of 2,2-diethoxyacetophenone and 0.1 part of ethylene glycol diacrylate are added, and the mixture is stirred and mixed evenly, and nitrogen is bubbled to deoxidize for 1 hour to obtain a cross-linked network precursor solution. The precursor solution is coated on a single-sided release silicon-free PET by a coating machine with a wet film thickness of 150μm, and the step speed is controlled to 5m / min and transferred to a UV curing machine (main peak 365nm), and the lamp power is adjusted to 1kW, and then transferred to a 40°C vacuum constant temperature oven for drying and rolling to obtain the product.

[0134] Example 4

[0135] 80 parts of butyl acrylate, 10 parts of benzyl acrylate, 10 parts of polyquaternium-51 monomer and 1 part of azobisisobutyronitrile were dissolved in tetrahydrofuran, the solid content was controlled to be 25%, nitrogen was bubbled in for deoxygenation for 1 hour, and then heated to 70°C for reaction for 12 hours under nitrogen environment. After the reaction was completed and cooled to room temperature, the product was transferred to a detergent (n-hexane: methanol = 8:2) for precipitation, and the precipitate was placed in a vacuum box and vacuum-degassed and dried at 60°C for 12 hours to remove the solvent and volatile monomers to obtain a low molecular weight linear polymer. Every 80 parts of low molecular weight linear polymer are dissolved in 100 parts of monomer mixture (80 parts of butyl acrylate, 10 parts of benzyl acrylate, 10 parts of methacrylamide propyl ammonium bis (trifluoromethanesulfonyl) imide salt monomer), 1 part of 2,2-diethoxyacetophenone and 0.1 part of ethylene glycol diacrylate are added, and the mixture is fully stirred and evenly mixed, and nitrogen is bubbled to deoxygenate for 1 hour to obtain a cross-linked network precursor solution. The precursor solution is coated on a single-sided release silicon-free PET by a coating machine with a wet film thickness of 150μm, and the step speed is controlled to 5m / min and transferred to a UV curing machine (main peak 365nm), and the lamp power is adjusted to 1kW, and then transferred to a 40℃ vacuum constant temperature oven for drying and rolling to obtain the product.

[0136] Comparative Example 1

[0137] 85 parts of butyl acrylate, 15 parts of benzyl acrylate and 1 part of azobisisobutyronitrile were dissolved in tetrahydrofuran, the solid content was controlled to be 25%, nitrogen was bubbled for deoxygenation for 1 hour, and then heated to 70°C for reaction for 12 hours in a nitrogen environment. After the reaction was completed and cooled to room temperature, the product was transferred to a detergent (n-hexane: methanol = 8:2) for precipitation, and the precipitate was placed in a vacuum box and vacuum degassed and dried at 60°C for 12 hours to remove the solvent and volatile monomers to obtain a low molecular weight linear polymer. Every 80 parts of the low molecular weight linear polymer was dissolved in 100 parts of a monomer mixture (85 parts of butyl acrylate, 15 parts of benzyl acrylate), 1 part of 2,2-diethoxyacetophenone and 0.1 part of ethylene glycol diacrylate were added, and the mixture was fully stirred and mixed, and nitrogen was bubbled for deoxygenation for 1 hour to obtain a cross-linked network precursor solution. The precursor liquid is coated on the single-sided release silicone-free PET by a coating machine with a wet film thickness of 150 μm, and the step speed is controlled to 5 m / min and transferred to a UV curing machine (main peak 365 nm), the lamp power is adjusted to 1 kW, and then transferred to a 40°C vacuum constant temperature oven for drying and then rolled up to obtain the product.

[0138] Comparative Example 2

[0139] 80 parts of butyl acrylate, 10 parts of benzyl acrylate, 10 parts of acryloyloxyethyl trimethyl ammonium bis (trifluoromethanesulfonyl) imide salt monomer and 1 part of azobisisobutyronitrile were dissolved in tetrahydrofuran, the solid content was controlled to be 25%, nitrogen was bubbled for deoxygenation for 1 hour, and then heated to 70°C for reaction for 12 hours under nitrogen environment. After the reaction was completed and cooled to room temperature, the product was transferred to a detergent (n-hexane: methanol = 8:2) for precipitation, and the precipitate was placed in a vacuum box and vacuum degassed and dried at 60°C for 12 hours to remove the solvent and volatile monomers to obtain a low molecular weight linear polymer. 66.6, 100, and 125 parts of low molecular weight linear polymer were dissolved in 100 parts of monomer mixture (butyl acrylate: benzyl acrylate: acryloyloxyethyl trimethyl ammonium bis (trifluoromethanesulfonyl) imide salt monomer = 80:10:10), 1 part of 2,2-diethoxyacetophenone and 0.1 part of ethylene glycol diacrylate were added, and the mixture was fully stirred and mixed, and nitrogen was bubbled for deoxygenation for 1 hour to obtain a cross-linked network precursor solution. The precursor solution was coated on a single-sided release silicon-free PET by a coating machine with a wet film thickness of 150μm, and the step speed was controlled to 5m / min and transferred to a UV curing machine (main peak 365nm), the lamp power was adjusted to 1kW, and then transferred to a 40℃ vacuum constant temperature oven for drying and rolling to obtain the product, that is, three samples with a low molecular weight linear polymer and monomer mixing ratio of 1:1.5, 1:1, and 1:0.8.

[0140] Comparative Example 3

[0141] 80 parts of butyl acrylate, 10 parts of benzyl acrylate, 10 parts of acryloyloxyethyl trimethyl ammonium bis (trifluoromethanesulfonyl) imide salt monomer and 1 part of azobisisobutyronitrile were dissolved in tetrahydrofuran, the solid content was controlled to be 25%, nitrogen was bubbled for deoxygenation for 1 hour, and then heated to 70°C for reaction for 12 hours under nitrogen environment. After the reaction was completed and cooled to room temperature, the product was transferred to a detergent (n-hexane: methanol = 8:2) for precipitation, and the precipitate was placed in a vacuum box and vacuum degassed and dried at 60°C for 12 hours to remove the solvent and volatile monomers to obtain a low molecular weight linear polymer. Every 80 parts of low molecular weight linear polymer was dissolved in 100 parts of monomer mixture (80 parts of butyl acrylate, 10 parts of benzyl acrylate, 10 parts of acryloyloxyethyl trimethyl ammonium bis (trifluoromethanesulfonyl) imide salt monomer), 1 part of 2,2-diethoxyacetophenone and 0.1 part of ethylene glycol diacrylate were added, and the mixture was stirred and mixed evenly, and nitrogen was bubbled to deoxidize for 1 hour to obtain a cross-linked network precursor solution. The precursor solution was coated on a single-sided release silicon-free PET by a coating machine with a wet film thickness of 150 μm, and the step speed was controlled to 5 m / min and transferred to a UV curing machine (main peak 365 nm), and the lamp power was adjusted to 0.7 kW, 0.8 kW, 0.9 kW, 1.1 kW, and 1.2 kW respectively, and then transferred to a 40°C vacuum constant temperature oven for drying and rolling to obtain the product.

[0142] Comparative Example 4

[0143] 80 parts of butyl acrylate, 10 parts of benzyl acrylate, 10 parts of acryloyloxyethyl trimethyl ammonium bis (trifluoromethanesulfonyl) imide salt monomer, 1 part of 2,2-diethoxyacetophenone and 0.1 part of ethylene glycol diacrylate were fully stirred and mixed and nitrogen was bubbled for deoxygenation for 1 hour to obtain a cross-linked network precursor solution. The precursor solution was coated on a single-sided release silicon-free PET by a coating machine with a wet film thickness of 150 μm, and the step speed was controlled to 5 m / min and transferred to a UV curing machine (main peak 365 nm), the lamp power was adjusted to 1 kW, and then transferred to a 40°C vacuum constant temperature oven for drying and rolling to obtain the product.

[0144] The bonding performance of the above adhesive materials was characterized. The main test content was a 90-degree peel test. The specific test method and standard were referred to GB / T 23260-2009 and GB / T328.11-2007. If there was no special description, the bonding substrate material was stainless steel 430BA.

[0145] Figure 2 The following is a comparison of the bonding performance of the samples in Example 1 on the surfaces of commonly used materials. Thanks to the high fluidity of the colloid, the adhesive exhibits excellent performance on difficult-to-bond surfaces including hydrophilic and hydrophobic surfaces, and has less performance loss when bonding in water.

[0146] Figure 3 The bonding performance of each embodiment is compared with that of comparative example 1. The performance of embodiment 2 is slightly worse, and the performance of comparative example 1 is extremely poor, indicating that the outstanding bonding performance of the adhesive relies on the interaction between the benzene ring, cations, and monomers in the cross-linked network, among which cations and monomers are the main sources.

[0147] Figure 4 and Figure 5 The performance attenuation tests were conducted after the adhesive was dry-bonded and immersed in tap water, and after being bonded in tap water and immersed in tap water for 4 weeks. It can be seen that the adhesive exhibits excellent long-term water resistance. When a certain external pressure is applied, the performance is improved by 15 to 30%, so it has the potential for long-term underwater service.

[0148] Figure 6 In order to test the influence of the ratio of low molecular weight polymer to cross-linking monomer on the bonding performance of the material, Example 1 was used as a benchmark, and the samples in Comparative Example 2 were combined to form control groups in which the ratios of low molecular weight linear polymer to monomer mixtures were 1:1.5, 1:1.25, 1:1, and 1:0.8, respectively; as the ratio of cross-linking monomers increased, the bonding performance first increased and then decreased, and the optimal ratio was between 1:1.1 and 1.30, and the optimal ratio was 1:1.25.

[0149] Figure 7To test the effect of UV curing machine power on material bonding performance, taking Example 1 as a benchmark and combining the samples in Comparative Example 3, a control group with UV lamp powers of 0.7kW, 0.8kW, 0.9kW, 1.0kW, 1.1kW, and 1.2kW respectively was formed; starting from 0.8kW, the greater the UV curing power, the better the crosslinking effect and the better the bonding performance of the material. The optimal power is between 0.9kW and 1.1kW, and the optimal is 1kW.

[0150] Figure 8 The performance comparison between the sample in Example 1 and a commercially available product with excellent performance shows that the adhesive has both outstanding dry bonding performance and underwater bonding performance.

[0151] This application focuses on the operation and application of underwater adhesive materials, and proposes new ideas for solving the problems of harsh underwater bonding conditions and long time consumption. At the same time, the adhesive has excellent performance and long-term water resistance. It can replace mechanical fasteners or liquid glue and is suitable for permanent bonding in water, plugging and repairing, or for building permanent waterproof and moisture-proof sealing structures. The adhesive material proposed in the present invention can be prepared by coating ultraviolet light curing and cross-linking, has a good industrial foundation, mature application and verification schemes, and has the potential for rapid industrialization and mass production.

[0152] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A method for preparing an underwater adhesive, characterized in that: include: Mixing raw materials including a first polymer monomer, a first ionic liquid monomer and / or a first cationic polymer, a first crosslinking agent, a first initiator, and an organic solvent, and performing a first reaction under a protective atmosphere to obtain a low molecular weight polymer; The low molecular weight polymer, the second polymer monomer and / or the second cationic polymer, the second ionic liquid monomer, the second cross-linking agent and the second initiator are mixed to obtain a precursor solution, and then a second reaction is performed to obtain the underwater adhesive; The first polymer monomer and the second polymer monomer each independently include one or more hydrophobic acrylic compounds; the first ionic liquid monomer and the second ionic liquid monomer each independently include one or more imide salts containing a double bond structure; the first cationic polymer and the second cationic polymer each independently include one or more polyquaternary ammonium salts containing a double bond structure; the weight average molecular weight of the low molecular weight polymer is 1-50kDa.

2. The method for preparing the underwater adhesive according to claim 1, characterized in that: One or more of the following conditions are met: (1) the first polymer monomer and the second polymer monomer each independently include one or more of benzyl acrylate, butyl acrylate, methyl acrylate, ethyl acrylate, cyclohexyl acrylate, ethyl methacrylate, butyl methacrylate, isopropyl methacrylate, isobornyl methacrylate, glycidyl methacrylate, methyl methacrylate, and benzyl methacrylate; (2) the first ionic liquid monomer and the second ionic liquid monomer each independently include one or more of acryloylalkyl trimethyl ammonium bis (trifluoromethanesulfonyl) imide salt, acryloyloxyethyl trimethyl ammonium bis (trifluoromethanesulfonyl) imide salt, methacryloyloxyethyl trimethyl ammonium bis (trifluoromethanesulfonyl) imide salt, and methacrylamide propyl ammonium bis (trifluoromethanesulfonyl) imide salt; (3) the first cationic polymer and the second cationic polymer each independently include one or more of polyquaternium-32, polyquaternium-28, and polyquaternium-51; (4) the first cross-linking agent and the second cross-linking agent each independently include one or more of an acrylate cross-linking agent and an acrylamide cross-linking agent; (5) the first initiator and the second initiator independently include one or more of a thermal initiator and a photoinitiator; (6) The organic solvent includes one or more of toluene, heptane, ethyl acetate, tetrahydrofuran, a heptane to toluene solution in a mass ratio of 1:(1-4), an ethyl acetate to toluene solution in a mass ratio of 1:(1-2), ethanol, dichloromethane, and chloroform.

3. The method for preparing the underwater adhesive according to claim 2, characterized in that: One or more of the following conditions are met: (1) The acrylate crosslinking agent includes one or more of 1,3-propylene glycol diacrylate, 1,4-butanediol diacrylate, 1,6-hexanediol diacrylate, ethylene glycol dimethacrylate, and ethylene glycol diacrylate; (2) The acrylamide cross-linking agent includes methylene bisacrylamide; (3) The first initiator is a thermal initiator, and the second initiator is a photoinitiator; (4) The thermal initiator includes one or more of azobisisobutyronitrile, azobisisovaleronitrile, azobisisoheptylnitrile, dimethyl azobisisobutyrate, 1-(cyano-1-methylethylazo)formamide, 1,1'-azo(cyanocyclohexane), dibenzoyl peroxide, diisopropylbenzene peroxide, and methyl ethyl ketone peroxide; (5) The photoinitiator includes one or more of 1-hydroxy-cyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, 2,4,6-trimethylbenzoyl diphenyl phosphine oxide, 2,4,6-trimethylbenzoyl phosphonic acid ethyl ester, 2-methyl-1-[4-methylthiophenyl]-2-morpholinyl-1-propanone, 2-isopropylthioxanthone, 4-dimethylamino-benzoic acid ethyl ester, benzoin dimethyl ether, methyl o-benzoylbenzoate, 4-chlorobenzophenone, 4-phenylbenzophenone, and 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone.

4. The method for preparing the underwater adhesive according to claim 1, characterized in that: One or more of the following conditions are met: (1) the molar ratio of the first polymer monomer to the first ionic liquid monomer and / or the first cationic polymer, and the molar ratio of the second polymer monomer to the second ionic liquid monomer and / or the second cationic polymer are each independently (3-9): 1; (2) the amount of the first crosslinking agent is no more than 1% of the total molar amount of the first polymer monomer, the first ionic liquid monomer and / or the first cationic polymer; (3) the amount of the second crosslinking agent is no more than 1% of the total molar amount of the second polymer monomer, the second ionic liquid monomer and / or the second cationic polymer; (4) the amount of the first initiator is 0.01% to 10% of the total molar amount of the first polymer monomer, the first ionic liquid monomer and / or the first cationic polymer; (5) the amount of the second initiator is 0.01% to 10% of the total molar amount of the second polymer monomer, the second ionic liquid monomer and / or the second cationic polymer; (6) The molar ratio of the low molecular weight polymer to the second polymer monomer is 1:(0.1-4).

5. The method for preparing the underwater adhesive according to claim 1, characterized in that: One or more of the following conditions are met: (1) the molar ratio of the first polymer monomer to the first ionic liquid monomer and / or the first cationic polymer, and the molar ratio of the second polymer monomer to the second ionic liquid monomer and / or the second cationic polymer are each independently (5-7): 1; (2) the amount of the first crosslinking agent is no more than 0.5% of the total molar amount of the first polymer monomer, the first ionic liquid monomer and / or the first cationic polymer; (3) the amount of the second crosslinking agent is no more than 0.5% of the total molar amount of the second polymer monomer, the second ionic liquid monomer and / or the second cationic polymer; (4) the amount of the first initiator is 1% of the total molar amount of the first polymer monomer, the first ionic liquid monomer and / or the first cationic polymer; (5) the amount of the second initiator is 1% of the total molar amount of the second polymer monomer, the second ionic liquid monomer and / or the second cationic polymer; (6) The molar ratio of the low molecular weight polymer to the second polymer monomer is 1:(0.5-1.5).

6. The method for preparing the underwater adhesive according to claim 1, characterized in that: One or more of the following conditions are met: (1) The first reaction is thermally initiated, with a reaction temperature of 40-110° C. and a reaction time of 1-24 h; (2) The second reaction is photoinduced with a power density of 1-1000 mW / cm 2 , wavelength 200-450nm, time 0.001-6h; (3) The weight average molecular weight of the low molecular weight polymer is 5-20 kDa; (4) During the first reaction, the total solid content is 15%-45%, preferably 20%-30%; (5) Before carrying out the first reaction, the system is deoxygenated.

7. The method for preparing the underwater adhesive according to any one of claims 1 to 6, characterized in that: After the first reaction is completed, the further step includes: transferring the reaction product into a detergent for precipitation and vacuum drying; and / or, The precursor solution is coated on the base film to obtain a wet film, and then the second reaction is carried out, and constant temperature vacuum drying is performed to obtain the adhesive.

8. The method for preparing the underwater adhesive according to claim 7, characterized in that: One or more of the following conditions are met: (1) The detergent comprises a mixture of a polar solvent and a non-polar solvent in a mass ratio of 1:(5-10); the polar solvent comprises methanol and / or ethanol, and the non-polar solvent comprises one or more of cyclohexane, n-hexane, and petroleum ether; (2) The vacuum degree of the vacuum drying is 0.1-1000 Pa, the temperature is 40-80° C., and the time is 6-24 h; (3) The thickness of the wet film is 1-1000 μm, preferably 25-250 μm; (4) The base film comprises one or more of PP, PC, PVC, PET, and metal foil, and has a thickness of 25-250 μm; (5) The temperature of the constant temperature vacuum drying is 30-80°C and the time is 0.5-30min.

9. An underwater adhesive, characterized in that: The underwater adhesive is prepared by the preparation method of the underwater adhesive according to any one of claims 1 to 8.

10. An underwater device, characterized in that: Including the underwater adhesive as described in claim 9.